The Relationship between architecture and noise pollution. - Balderrama, Alvaro (Technische Hochschule Ostwestfalen-Lippe, IDS Institut für Designstrategien, 2021)
Urban expansion and densification bring opportunities and challenges, and transforming cities into vibrant, sustainable and resilient living places has become a key global priority (European Commission, 2021). This is reflected internationally through the “2030 Agenda for Sustainable Development”, which is part of a global call to rethink and redesign urban environments through innovative solutions that address multiple issues including noise pollution, considered a major environmental threat with substantial negative impact on public health and the economy. The way that people perceive and engage in their acoustic environment can play a significant role in the advancement towards the Sustainable Development Goals, especially in Goal 3 - “ensure healthy lives and promote well-being”, and Goal 11 - “make cities inclusive, safe, resilient and sustainable”. While the relationship between architecture and noise pollution is still an ongoing discussion internationally, the progress of sustainable construction in the past decades shows the potential alignment of building practices with sustainable strategies that can lead to benefits for society, the environment and the economy. This article addresses some concepts that might be relevant at the time of discussing the role of architecture in relation to urban noise, giving special attention to the design of facades since these components of the building envelope tend to be in direct contact with sound sources in urban environments.
Keywords: Lärmschutz; Stadtgestaltung; Gebäudehülle; Oberflächengestaltung; Umweltwahrnehmung; Nachhaltige Entwicklung; Soundscape; Sustainable Development Goals; Agenda 2030 für nachhaltige Entwicklung